Spiritual wellbeing in sub-Saharan Africa: the meaning and prevalence of 'feeling at peace'. (1st April 2011) - Selman, L; Harding, R; Higginson, I J; Gysels, M; Speck, P; ,
Abstract : Abstract: Introduction and aims: Palliative care (PC) is an urgent public health issue in Africa, but evidence to inform the spiritual dimension of PC is lacking. Feeling at peace is strongly correlated with spiritual wellbeing (SWB), and occurs in spiritual measures validated cross-culturally in PC populations. We aimed to: Determine levels of SWB among PC patients in South Africa and Uganda. Explore how patients interpret 'feeling at peace'. Methods: Cross-sectional survey using the APCA African Palliative Outcome Scale (POS) item: 'Over the past 3 days, have you felt at peace?' ('0= no, not at all' – '5= yes, all the time'). Semi-structured interviews including cognitive interviewing of the POS, analysed thematically. Results: 285 patients surveyed; mean age 40.1; 69.1% women; diagnosis: 80.7% HIV; 17.7% cancer; 1.6% other. Mean peace score 2.92. 27.0% scored 0–1. 72 patients interviewed in 7 languages. Mean age 45.1; 66.7% women; diagnosis: 59.7% HIV; 40.3% cancer. Interpretations of peace fell into four categories: perception of self/ world (peace as a feeling/acceptance/experience); relationship with others; relationship with God; health-related. Barriers to peace included uncontrolled pain, stigma, economic/family worries. Conclusion: This is the first study into the SWB of PC patients in sub-Saharan Africa. >25% of patients had not felt at peace in the previous 3 days, or only very rarely. Feeling at peace was interpreted in existential, social, religious and physical terms. Asking whether a patient feels at peace may be effective in eliciting concerns in African PC.